2015
DOI: 10.1111/evo.12800
|View full text |Cite
|
Sign up to set email alerts
|

Prey from the eyes of predators: Color discriminability of aposematic and mimetic butterflies from an avian visual perspective

Abstract: Predation exerts strong selection on mimetic butterfly wing color patterns, which also serve other functions such as sexual selection. Therefore, specific selection pressures may affect the sexes and signal components differentially. We tested three predictions about the evolution of mimetic resemblance by comparing wing coloration of aposematic butterflies and their Batesian mimics: (a) females gain greater mimetic advantage than males and therefore are better mimics, (b) due to intersexual genetic correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 95 publications
(154 reference statements)
2
46
1
Order By: Relevance
“…11.2). The female has been considered to be a Batesian mimic (Su et al 2015). The larvae feed on Violaceae plants similar to many other related species in the tribe Argynnini in Japan.…”
Section: )mentioning
confidence: 99%
“…11.2). The female has been considered to be a Batesian mimic (Su et al 2015). The larvae feed on Violaceae plants similar to many other related species in the tribe Argynnini in Japan.…”
Section: )mentioning
confidence: 99%
“…Ohsaki (1995) proposed that females disproportionately benefit from evolving mimicry and indeed found that wild‐caught nonmimetic P. polytes females had nearly double the proportion of beak marks on their wings compared to P. polytes males (which are always nonmimetic). More recently, Su, Lim, and Kunte (2015) tested the mimetic resemblance of several sexually monomorphic and female‐limited Batesian mimics, including P. polytes , using bird vision models. Their results show that females are better mimics than males of sexually monomorphic taxa, and that female‐limited mimics are as good as sexually monomorphic mimics, supporting the idea that females disproportionately benefit from mimicry.…”
Section: Discussionmentioning
confidence: 99%
“…Wallace (1866) introduced the idea of warning signaling (later termed aposematism) during his studies of butterflies in tropical Asia, but further use of tropical Asian butterflies for aposematism and mimicry studies has been extremely limited (Ex: Yamauchi, 1993; Kitamura & Imafuku, 2010; Kunte et al., 2014; Su et al., 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Species possibly belonging to mimicry rings were separated based on (Kunte, 2008; Su et al., 2015), and additional regional species were added based on visual similarity and host plant information. These included five mimicry rings (names based on the most common aposematic genus of the ring); Danaus , Tirumala , Euploea (Danainae: Nymphalidae), Pachliopta (Papilionidae), and Delias (Pieridae).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation